Transcriptomic Analysis of Dysregulated Genes of the nDNA-mtDNA Axis in a Mouse Model of Dilated Cardiomyopathy - Ziemann, Mark; Wu, Wei; Deng, Xiu-Ling; Du, Xiao-Jun (Frontiers in Genetics, 2022)
Background: Mitochondrial dysfunction is implicated in the development of cardiomyopathy and heart failure. Transcription of mitochondrial DNA (mtDNA) encoded genes and subsequent protein synthesis are tightly regulated by nuclear DNA (nDNA) encoded proteins forming the nDNA-mtDNA axis. The scale of abnormalities in this axis in dilated cardiomyopathy (DCM) is unclear. We previously demonstrated, in a mouse DCM model with cardiac Mst1 overexpression, extensive downregulation of mitochondrial genes and mitochondrial dysfunction. Using the pre-acquired transcriptome sequencing database, we studied expression of gene sets of the nDNA-mtDNA axis. Methods: Using RNA-sequencing data from DCM hearts of mice at early and severe disease stages, transcriptome was performed for dysregulated nDNA-encoded gene sets that govern mtDNA transcription and in situ protein synthesis. To validate gene data, expression of a panel of proteins was determined by immunoblotting. Results: Relative to littermate controls, DCM hearts showed significant downregulation of all mtDNA encoded mRNAs, as well as mtDNA transcriptional activators. Downregulation was also evident for gene sets of mt-rRNA processing, aminoacyl-tRNA synthases, and mitoribosome subunits for in situ protein synthesis. Multiple downregulated genes belong to mitochondrial protein-importing machinery indicating compromised importing of proteins for mtDNA transcription and translation. Diverse changes were genes of mtRNA-binding proteins that govern maturation and stability of mtDNA-derived RNAs. Expression of mtDNA replicome genes was largely unchanged. These changes were similarly observed in mouse hearts at early and severe stages of DCM. Conclusion: Transcriptome revealed in our DCM model dysregulation of multiple gene sets of the nDNA-mtDNA axis that is expected to interfere with mtDNA transcription and in situ protein synthesis. Dysfunction of the nDNA-mtDNA axis might contribute to mitochondrial dysfunction and ultimately development of DCM.